2016
DOI: 10.1158/1940-6207.capr-15-0350
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Microbiota Associated with Higher Grade Cervical Intraepithelial Neoplasia in Women Infected with High-Risk Human Papillomaviruses

Abstract: It is increasingly recognized that microbes that reside in and on human body sites play major roles in modifying the pathogenesis of several diseases including cancer. However, specific microbes or microbial communities that can be mechanistically linked to cervical carcinogenesis remain largely unexplored. The purpose of the study was to examine the association between cervical microbiota and high-grade cervical intraepithelial neoplasia (CIN 2+) in women infected with high-risk (HR) human papillomaviruses (H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
128
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 78 publications
(87 reference statements)
12
128
0
3
Order By: Relevance
“…However, further studies have shown that under the hypoxic conditions of the vagina, bacteria are unable to make significant levels of H 2 O 2 , which is subsequently present at low levels in the human vagina, and these physiological levels are unable to inhibit growth of BV-associated species in vitro [83, 84]. The observation that L. iners often predominates in the presence of HPV infection [53] and CIN [56, 57] may also be linked to the relative instability of this CST in comparison to other Lactobacillus spp.-dominant CSTs [21], allowing growth of strict anaerobes resulting in transition to CST IV, which as previously discussed is commonly found in association with dysplasia [5456]. However, vaginal lactobacilli can exhibit cytotoxic effects on cervical tumour cells in vitro, independent of pH and lactic acid, without the same effects on normal cervical cells [85].…”
Section: Potential Mechanisms Of Vaginal Microbiota-mediated Cervicalmentioning
confidence: 99%
See 3 more Smart Citations
“…However, further studies have shown that under the hypoxic conditions of the vagina, bacteria are unable to make significant levels of H 2 O 2 , which is subsequently present at low levels in the human vagina, and these physiological levels are unable to inhibit growth of BV-associated species in vitro [83, 84]. The observation that L. iners often predominates in the presence of HPV infection [53] and CIN [56, 57] may also be linked to the relative instability of this CST in comparison to other Lactobacillus spp.-dominant CSTs [21], allowing growth of strict anaerobes resulting in transition to CST IV, which as previously discussed is commonly found in association with dysplasia [5456]. However, vaginal lactobacilli can exhibit cytotoxic effects on cervical tumour cells in vitro, independent of pH and lactic acid, without the same effects on normal cervical cells [85].…”
Section: Potential Mechanisms Of Vaginal Microbiota-mediated Cervicalmentioning
confidence: 99%
“…The HPV E6 oncoprotein [98] is also known to use this mechanism which results in the loss of E1 and E2 genes, and subsequently uncontrolled transcription of E6 and E7 enabling increased cellular proliferation, and decrease apoptosis [99]. Despite this evidence, a recent study by Piyathilake and co-workers [57] did not report any significance associated between VMB composition and oxidative stress-induced DNA damage.…”
Section: Potential Mechanisms Of Vaginal Microbiota-mediated Cervicalmentioning
confidence: 99%
See 2 more Smart Citations
“…It is increasingly recognized that microbes resident in the human body play major roles in modifying carcinogenesis [7,8]. The effects of inhibition and degradation via the ubiquitin pathway of p53 by E6 and the inhibition of the retinoblastoma gene and subsequent released actions of E2F transcription factors are centered on essential loss of control of check-points in epithelial cell proliferation.…”
Section: Molecular Eventsmentioning
confidence: 99%